Uji Beberapa Dosis Pupuk Vermikompos Pada Tanaman Kacang Hijau (Vigna radiata L.) - Ilvia Ayunita; Arifien Mansyoer; Sampoerno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The used of organic fertilizers that environment friendly and do not damage nature is the best solution in the cultivation of green beans (Vigna radiata L.). Vermicompost organic fertilizer is one of the more qualified than the other organic fertilizers. This organic fertilizer is the result of composting without worms.The purpose of this study was to examine the use of multiple doses of vermicompost fertilizer and get a dose of fertilizer is best for the growth and production of green beans. This research has been conducted in the gauze, experimental garden of the Faculty of Agriculture, University of Riau, from December 2013 to February 2014. This study was performed experimentally using a completely randomized design (CRD), 5 treatments and 3 replicates with 6 plants per experimental unit, 3 plants used as a sample. The parameters measured were plant height (cm), number of primary branches (branches), days to flowering (days), pod formation age (days), maturity (days), number of pods per plant pithy (pieces), the number of empty pods per plant (pieces), dried seed weight per plant (g) and weight of 100 seeds (g). The data analysis results were significant statistical test followed by least significant difference (LSD) at the 5% level. The results of this study indicate that vermicompost fertilizer on green beans significantly affect flowering, pod formation age, maturity and weight of 100 seeds. Vermicompost fertilizer at a dose of 40 g/polybag give the best results on a number of parameters compared to the other doses. Keywords : Fertilizer, Vermicompost, Dose, Green Bean